2023
DOI: 10.1002/ijop.12891
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of attentional bias in meditators: An ERP study

Abstract: Attentional bias is closely related to individual mental health. To explore the effect of mindfulness meditation on attentional bias, we use the dot‐probe task to measure and compare the attentional bias of 16 Shaolin monks with meditation experience (meditator group) and 18 ordinary people without meditation experience (control group). The results were as follows: (1) The control group showed attentional bias to anger stimuli, while the meditator group did not show attentional bias; (2) The P1 amplitude induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Generally, it is modulated by attention and associated with the initiation of an executive process when identifying unusual stimuli ( 20 , 42 ). The P2 is an indicator of attentional engagement during cognitive processing ( 43 ). In our study, meditators showed higher P2 amplitudes and shorter RTs, suggesting more efficient attentional functioning during stimulus perception, although the task accuracy rate was approximately the same for both groups (potentially due to a ceiling effect).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it is modulated by attention and associated with the initiation of an executive process when identifying unusual stimuli ( 20 , 42 ). The P2 is an indicator of attentional engagement during cognitive processing ( 43 ). In our study, meditators showed higher P2 amplitudes and shorter RTs, suggesting more efficient attentional functioning during stimulus perception, although the task accuracy rate was approximately the same for both groups (potentially due to a ceiling effect).…”
Section: Discussionmentioning
confidence: 99%